PERAN LAYANAN KONSELING INDIVIDUAL DENGAN PENDEKATAN COGNITIVE BEHAVIOR THERAPY DALAM MENANGANI PERILAKU SIKLOTIMIA PADA SISWA KELAS IX SMP MUHAMMADIYAH 2 SURAKARTA TAHUN AJARAN 2024/2025: Penelitian Tindakan Bimbingan dan Konseling - Putri Heryani, Salsa; Adi Putro, Eko; Jawandi, Ahmad (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
ABSTRACT The purpose of this study was to determine the role of individual counseling services with a Cognitive Behavior Therapy (CBT) approach in dealing with cyclothymic behavior in grade IX students of Muhammadiyah 2 Junior High School Surakarta in the 2024/2025 Academic Year. This research was conducted at Muhammadiyah 2 Junior High School Surakarta. The subject in this study was one high school student. This research is a Guidance and Counseling Action Research (PTBK) which was carried out in 3 cycles. Each cycle consists of 4 stages, namely, planning, action, observation, and reflection. Data collection techniques used in this study were observation, interviews and documentation. In the first cycle of action research, the results obtained cyclothymic behavior decreased, but there were still several indicators that had not been resolved properly with a percentage of 70%. Next, these results were evaluated and then the researcher provided action in the second cycle. In the second cycle of action research, the results obtained cyclothymic behavior decreased by 48.33%. Furthermore, these results were re-evaluated and then the researcher provided action in the third cycle. In the third cycle of action research, the results showed a decrease in cyclothymic behavior by 21.66%, reaching the target set by the researcher. It can be concluded that individual counseling services using the Cognitive Behavior Therapy (CBT) approach can address cyclothymic behavior in ninth-grade students at SMP Muhammadiyah 2 Surakarta in the 2024/2025 academic year.